A nickel-based composite electrode and a method for preparing the same
Patent Information
- Application Number
- CN202511748090.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-26
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-11-26
AI Technical Summary
该文献对于其采用的短时间热刺激的方式能否抑制晶界处的镍富集未进行研究
本发明能够抑制电极中晶界处的镍富集,从而提高了晶界处的离子电导率。同时,本发明的镍基复合电极中的电解质晶粒内部能够具有较高的镍含量,其离子导电性和电子导电性均可明显增加,具有混合离子导体的特征。因此,本发明的镍基复合电极具有提升的电导率和综合性能。而且相较于现有的烧结方法,本发明还具有工艺简单、烧结时间短、效率高、降低能耗等优点。
Smart Images

Figure CN121964676B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a nickel-based composite electrode and its preparation method, belonging to the field of solid oxide battery technology. Background Technology
[0002] Solid oxide batteries (SOCs) are all-solid-state ceramic devices that function as both solid oxide fuel cells (SOFCs) and solid oxide electrolyzers (SOECs). SOFCs can convert the chemical energy of H2, natural gas, and hydrocarbons into electrical energy, while SOECs can convert and store solar, wind, and other renewable energy sources into hydrogen fuel.
[0003] SOCs mainly consist of an anode, a cathode, and an electrolyte. The most commonly used material for the fuel electrode (i.e., the anode) of SOCs is a nickel-based composite material, including nickel metal with oxygen ion conductor yttrium-stabilized zirconium oxide (YSZ), gadolinium oxide-doped cerium oxide (GDC), or proton conductor BaZr. 0.1 Ce 0.7 Y 0.2 O 3-δ (BZCY) fuel electrodes with mixed sintering structure have a wide range of applications.
[0004] However, severe nickel diffusion is a common problem in fuel electrodes during high-temperature sintering. For example, microstructural characterization revealed significant Ni enrichment at the YSZ grain boundaries of the SOFC anode support in fuel cells. This makes the grain boundaries a major factor in blocking oxygen ion transport, significantly reducing the overall ionic conductivity and performance of the fuel electrode.
[0005] CN117438624A discloses a method for modifying solid oxide fuel cells, wherein the anode modification steps are as follows: (1) La2O3, CaCO3, TiO2, and NiO raw materials are ball-milled with zirconia balls using ethanol as a medium. After the ethanol is evaporated by heating, the fully mixed powder is subjected to a two-stage high-temperature heat treatment. The two-stage high-temperature heat treatment is first performed at 1100℃ for 20h, and then at 1350℃ for 20h to obtain a single-phase LCTN electrode substrate; (2) The quartz chamber is evacuated, and in an H2 / N2 atmosphere, the obtained LCTN single-phase electrode substrate is excited by a thermal stimulation method in the quartz chamber using carbon paper as a heating source. The thermal stimulation method is performed at 1400℃ for 10s, and metallic Ni nanoparticles appear on the LCTN surface. This method uses short-time thermal stimulation to inhibit the growth and coarsening of Ni metal particles, thereby obtaining Ni nanoparticles with high particle density and high active site concentration. This paper does not investigate whether the short-duration thermal stimulation method used can suppress nickel enrichment at grain boundaries.
[0006] Developing novel nickel-based composite electrodes and their preparation methods to suppress nickel enrichment at grain boundaries has become one of the urgent problems to be solved in this field. Summary of the Invention
[0007] To address the aforementioned technical problems, the present invention aims to provide a nickel-based composite electrode and its preparation method. The present invention can suppress nickel enrichment at grain boundaries in the electrode, thereby improving the electrode's conductivity.
[0008] To achieve the above objectives, the first aspect of the present invention provides a method for preparing a nickel-based composite electrode, comprising the following steps: (1) A mixture containing nickel compound and electrolyte is molded to obtain a nickel-based composite electrode precursor; (2) The nickel-based composite electrode precursor is pre-fired, then flash-fired at 1500~3000℃, and then annealed to obtain the nickel-based composite electrode.
[0009] According to a specific embodiment of the present invention, preferably, in step (1), the nickel compound includes nickel oxide (NiO) and the like.
[0010] According to a specific embodiment of the present invention, preferably, in step (1), the electrolyte is an electrolyte for a solid oxide battery. More preferably, the electrolyte includes one or more of yttrium-stabilized zirconium oxide (YSZ), gadolinium-doped cerium oxide (GDC), scandium-stabilized zirconium oxide (ScSZ), samarium-doped cerium oxide (SDC), and perovskite oxides. Even more preferably, the electrolyte includes yttrium-stabilized zirconium oxide and / or gadolinium-doped cerium oxide.
[0011] According to a specific embodiment of the present invention, preferably, in step (1), the mass ratio of the nickel compound to the electrolyte is (10~80):(90~20).
[0012] According to a specific embodiment of the present invention, preferably, in step (2), the pre-firing temperature is 400~600℃, the pre-firing time is 1~3h, and the pre-firing is carried out in an oxidizing gas atmosphere.
[0013] According to a specific embodiment of the present invention, preferably, in step (2), the high-temperature flash burning time is 1~60s.
[0014] According to a specific embodiment of the present invention, preferably, in step (2), the high-temperature flash burning is achieved by Joule heating.
[0015] According to a specific embodiment of the present invention, preferably, in step (2), the high-temperature flash calcination includes: heating to 1500-3000°C at a heating rate of 20-500°C / s, maintaining the temperature at 1500-3000°C for 1-60s for high-temperature flash calcination, and then cooling to room temperature at a cooling rate of 100-1000°C / s. More preferably, the high-temperature flash calcination includes the following process: placing the pre-calcined product in the middle of the carbon material, applying an electric current to the carbon material, controlling the heating rate to be 20-500°C / s, heating to 1500-3000°C and maintaining the temperature for 1-60s for high-temperature flash calcination, then stopping the application of the electric current, and cooling to room temperature at a cooling rate of 100-1000°C / s to obtain the product after high-temperature flash calcination.
[0016] According to a specific embodiment of the present invention, preferably, in step (2), the annealing temperature is 300~1400℃, the annealing time is 0.5~20h, and the annealing is carried out in an oxidizing gas atmosphere.
[0017] A second aspect of the present invention provides a nickel-based composite electrode, which is prepared by the above-described method for preparing a nickel-based composite electrode.
[0018] According to a specific embodiment of the present invention, preferably, the difference between the Ni element content at the grain boundaries of the electrolyte and the Ni element content in the grains of the nickel-based composite electrode is less than 6%.
[0019] According to a specific embodiment of the present invention, preferably, the Ni content in the electrolyte grains of the nickel-based composite electrode is 1-15%.
[0020] The present invention has at least the following beneficial effects: This invention can suppress nickel enrichment at grain boundaries in the electrode, thereby improving the ionic conductivity at the grain boundaries. Simultaneously, the electrolyte grains in the nickel-based composite electrode of this invention can have a high nickel content, significantly increasing both ionic and electronic conductivity, exhibiting characteristics of a mixed ionic conductor. Therefore, the nickel-based composite electrode of this invention possesses improved conductivity and overall performance. Moreover, compared to existing sintering methods, this invention also has advantages such as simple process, short sintering time, high efficiency, and reduced energy consumption. Attached Figure Description
[0021] Figure 1 STEM-HAADF images and EDS-mapping images of the grains and grain boundaries of the two nickel-based composite electrodes prepared in Example 1.
[0022] Figure 2 STEM-HAADF and EDS-mapping images of the YSZ grain boundaries of a commercially available SOFC anode support.
[0023] Figure 3 Electrochemical impedance spectroscopy (EIS) spectra of 20N-YSZ from Comparative Example 3 and 20N-YSZ-UHS-800 and 20N-YSZ-UHS-1200 from Example 1, obtained by testing at 200℃ and 800℃ respectively.
[0024] Figure 4 The images show STEM-HAADF and EDS-mapping diagrams of the nickel-based composite electrode in Example 2 at the grains and grain boundaries, as well as electrochemical impedance spectroscopy (EIS) spectra of the 20N-GDC electrode in Comparative Example 4 and the nickel-based composite electrode in Example 2, obtained by testing at 200°C and 800°C, respectively.
[0025] Figure 5 The images show STEM-HAADF and EDS-mapping diagrams of the nickel-based composite electrode in Example 3 at the grains and grain boundaries, as well as the electrochemical impedance spectroscopy obtained at 250°C.
[0026] Figure 6 The images show STEM-HAADF and EDS-mapping diagrams of the nickel-based composite electrode in Example 4 at the grains and grain boundaries, as well as the electrochemical impedance spectroscopy obtained at 250°C.
[0027] Figure 7 The images show STEM-HAADF and EDS-mapping diagrams of the nickel-based composite electrode in Comparative Example 1 at the grains and grain boundaries, as well as the electrochemical impedance spectroscopy obtained at 250 °C.
[0028] Figure 8 The images show STEM-HAADF and EDS-mapping diagrams of the nickel-based composite electrode in Comparative Example 2 at the grains and grain boundaries, as well as the electrochemical impedance spectroscopy obtained at 250 °C. Detailed Implementation
[0029] To provide a clearer understanding of the technical features, objectives, and beneficial effects of the present invention, the present invention will now be described in detail below, but this should not be construed as limiting the scope of the invention.
[0030] It should be noted that, unless otherwise specified, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.
[0031] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods.
[0032] It is to be understood that the terms "comprise", "comprising" and / or "contain", when used herein, specify the presence of the stated features, integers, steps, components or combinations thereof, but do not exclude the presence or addition of one or more other features, integers, steps, components or combinations thereof.
[0033] The endpoints and any values of the ranges disclosed in the present invention are not limited to such precise ranges or values, and these ranges or values should be construed as including values approximating these ranges or values. For numerical ranges, the endpoints of each range, between the endpoints of each range and the individual point values, and between the individual point values may be combined with each other to obtain one or more new numerical ranges, which shall be regarded as being specifically disclosed in the present invention.
[0034] According to a specific embodiment of the first aspect of the present invention, the present invention provides a method for preparing a nickel-based composite electrode, comprising the following steps: (1) molding a mixture comprising a nickel compound and an electrolyte to obtain a nickel-based composite electrode precursor; (2) pre-sintering the nickel-based composite electrode precursor, then performing high-temperature flash sintering at 1500 to 3000°C, and then performing annealing to obtain the nickel-based composite electrode.
[0035] In some embodiments, in step (1), the nickel compound includes nickel oxide (NiO) and the like.
[0036] In some embodiments, in step (1), the electrolyte is an electrolyte for solid oxide cells. Preferably, the electrolyte includes one or more of yttria-stabilized zirconia (YSZ), gadolinia-doped ceria (GDC), scandia-stabilized zirconia (ScSZ), samaria-doped ceria (SDC), perovskite oxides, and the like. Specifically, the perovskite oxide includes BZY(BaZr 1-a Y a O 3-δ , 0<a≤0.5), BCY(BaCe 1-b Y b O 3-δ , 0<b≤0.5), and BZCY(BaZr 1-c-d Ce c Y d O 3-δ , 0.5<c<1, 0<d≤0.5) and the like, one or two or more thereof. More preferably, the electrolyte includes yttria-stabilized zirconia and / or gadolinia-doped ceria. These electrolytes may employ electrolytes for solid oxide cells in the prior art.
[0037] In some embodiments, in step (1), the mass ratio of the nickel compound to the electrolyte is (10~80):(90~20), for example, 10:90, 20:80, 30:70, 40:60, 50:50, 60:40, 70:30 or 80:20, etc.
[0038] In some embodiments, in step (1), the mixture comprising the nickel compound and the electrolyte may further comprise a pore-forming agent. The pore-forming agent may include, for example, starch. The amount of the pore-forming agent may be 1 to 15 parts by mass relative to the total amount of 100 parts by mass of the nickel compound and the electrolyte.
[0039] In some embodiments, in step (1), the mixture comprising the nickel compound and the electrolyte may further comprise a solvent. The solvent may comprise water and / or an organic solvent, such as an alcohol compound, specifically ethanol and / or isopropanol. The amount of solvent used may be 30 to 120 parts by mass relative to the total amount of 100 parts by mass of the nickel compound and the electrolyte.
[0040] In some embodiments, in step (1), the mixture comprising the nickel compound and the electrolyte can be prepared by mechanically mixing the nickel compound, the electrolyte, and other selectively included components (such as the pore-forming agent and / or solvent described above). The mechanical mixing may, for example, include ball milling. If the mixture contains a solvent, it may be dried after mixing and then molded.
[0041] In some embodiments, the molding process in step (1) may include pressing, etc.
[0042] In some embodiments, in step (2), the pre-firing temperature is 400~600°C, the pre-firing time is 1~3 hours, and the pre-firing is carried out in an oxidizing gas atmosphere. The oxidizing gas can be, for example, air. The pre-firing heating rate is preferably 2~5°C / min. After the pre-firing is completed, the temperature can be cooled to room temperature before subsequent high-temperature flash firing.
[0043] This invention, by controlling the pre-calcination temperature and time within the aforementioned range, enables the added pore-forming agents and other components to fully decompose, preventing defects such as electrode cracks caused by residual organic matter or sudden decomposition generating gas during subsequent high-temperature flash calcination. Furthermore, it allows for preliminary densification of the pre-calcined product, giving it suitable strength and preventing deformation or collapse during subsequent high-temperature flash calcination. Simultaneously, it establishes a preliminary interaction between nickel and the electrolyte, laying the foundation for subsequent electrode microstructure construction. If the pre-calcination temperature and time are below the aforementioned range, the above effects and benefits are difficult to fully realize. If the pre-calcination temperature and time are above the aforementioned range, it may lead to excessive sintering driving force between particles, causing excessive particle growth and agglomeration, resulting in uneven electrode grain size and poor microstructure.
[0044] In some embodiments, in step (2), the high-temperature flash burning time is 1~60s.
[0045] In some embodiments, in step (2), the high-temperature flash burning is achieved by Joule heating.
[0046] Specifically, the high-temperature flash burning includes: heating to 1500-3000℃ at a heating rate of 20-500℃ / s, maintaining the temperature at 1500-3000℃ for 1-60 seconds for high-temperature flash burning, and then cooling to room temperature at a cooling rate of 100-1000℃ / s. Preferably, the high-temperature flash burning temperature is 1500-1800℃, the time is 10-20 seconds, the heating rate is 100-200℃ / s, and the cooling rate is 200-800℃ / s.
[0047] More specifically, the high-temperature flash calcination includes the following process: placing the pre-calcined product in the middle of a carbon material, applying an electric current to the carbon material, controlling the heating rate at 20~500℃ / s (preferably 100~200℃ / s), heating to 1500~3000℃ (preferably 1500~1800℃) and holding for 1~60s (preferably 10~20s) for high-temperature flash calcination, then stopping the application of the current, and cooling to room temperature at a cooling rate of 100~1000℃ / s (preferably 200~800℃ / s) to obtain the product after high-temperature flash calcination. Applying the current to the carbon material is achieved by connecting electrodes to both ends of the carbon material. The carbon material is mainly used to conduct current to achieve Joule heating. The carbon material can be folded in half, and the pre-calcined product can be sandwiched in the middle of the carbon material, so that both the upper and lower surfaces of the pre-calcined product are in contact with the carbon material. Connecting external electrodes to both ends of the carbon material allows current to pass through and facilitates the uniformity of Joule heating. The applied current can be adjusted based on the heating rate described above, as long as the heating rate remains within the aforementioned range. The carbon material can be, for example, carbon fiber felt, carbon paper, or carbon cloth. The high-temperature flash calcination is preferably performed in a vacuum environment; performing it in an air atmosphere will affect the diffusion of Ni into the grains.
[0048] This invention employs Joule heating for high-temperature flash sintering, utilizing the rapid heating and cooling characteristics of Joule heating. By controlling the temperature, time, and heating / cooling rates within the aforementioned range, rapid sintering of nickel-based composite electrodes can be achieved. During rapid sintering, the material surface melts at high temperatures to form a liquid phase, promoting interparticle adhesion and enhancing the bonding force between particles. This also promotes particle growth and fusion, resulting in a more regular microstructure. Simultaneously, the inventors unexpectedly discovered that by employing high-temperature flash sintering and controlling its conditions within the aforementioned range, nickel atom activity is intensified. Nickel atoms can enter the electrolyte grains through vacancies, interstitials, and other defects in the electrolyte lattice, resulting in a higher nickel content (elemental doping) within the electrolyte grains of the electrode. In other words, rapid sintering during the high-temperature operation of this invention achieves Ni dispersion within the grains. Furthermore, because the high-temperature holding time and cooling time are both short, Ni precipitation and enrichment at grain boundaries are suppressed. If the temperature and time of high-temperature flash sintering are below the aforementioned range, sintering will be insufficient, and the aforementioned effects will be difficult to achieve. If the temperature and time of high-temperature flash burning exceed the above ranges, the microstructure of the material may be damaged, resulting in excessive stress that is difficult to eliminate even with subsequent low-temperature annealing. If the cooling rate of high-temperature flash burning is below the above ranges, Ni enrichment occurs at the grain boundaries, and the nickel content inside the grains is too low.
[0049] Furthermore, this invention places the pre-calcined product in the middle of a carbon material for high-temperature flash calcination. The carbon material has excellent electrical conductivity, ensuring uniform current flow throughout the system, allowing for uniform heating and guaranteeing the stability and uniformity of the flash calcination process. This contributes to obtaining electrodes with uniform performance. If carbon material is not used, and the two ends of the pre-calcined product are directly connected to the electrode, the current may not be able to flow uniformly onto the material, leading to structural and performance inhomogeneities in the electrode. Moreover, without the additional resistive heating provided by the carbon material, relying solely on the resistive heating between the electrode and the pre-calcined product may significantly slow down the heating rate, making rapid flash calcination difficult. This hinders the full effectiveness of suppressing nickel accumulation at grain boundaries and increasing the nickel content within the electrolyte grains.
[0050] In some embodiments, in step (2), the annealing temperature is 300~1400℃, preferably 300~1200℃, and more preferably 800~1200℃.
[0051] In some embodiments, in step (2), the annealing time is 0.5 to 20 hours, preferably 0.5 to 5 hours, and more preferably 1 to 3 hours.
[0052] In some embodiments, in step (2), the annealing heating rate is 2~5℃ / min, and the cooling rate is 2~5℃ / min. After cooling to room temperature, a nickel-based composite electrode is obtained.
[0053] In some embodiments, in step (2), the annealing is performed in an oxidizing gas atmosphere. The oxidizing gas may be, for example, air.
[0054] This invention employs low-temperature annealing after high-temperature flash firing. By controlling the temperature and time of low-temperature annealing within the aforementioned range, it can eliminate material stress, allowing atoms to rearrange and relax to a certain extent, reducing the risk of electrode cracking or deformation. Simultaneously, it can achieve more uniform grain size, further optimizing the electrode's microstructure. If the temperature and time of low-temperature annealing are below the aforementioned range, the effects of stress elimination and microstructure optimization are difficult to fully realize. If the temperature and time of low-temperature annealing are above the aforementioned range, it may lead to excessive grain growth, resulting in uneven grain size, and may also cause thermal damage and deformation to the electrode.
[0055] In some embodiments, the preparation method of the nickel-based composite electrode of the present invention specifically includes the following steps: Step 1, Mixing and Molding: Weigh the nickel compound and electrolyte at a mass ratio of (10~80):(90~20), then add them to a ball mill jar, along with an appropriate amount of pore-forming agent and solvent. After adding grinding beads, place the mixture in a ball mill and grind it evenly. Then pour it out and dry it to obtain a powder mixture containing nickel compound and electrolyte. Next, add the powder mixture containing nickel compound and electrolyte to an agate grinding media and grind it evenly. Weigh an appropriate amount of the powder mixture and place it in a tableting mold. After tableting under 40~80MPa conditions, a nickel-based composite electrode precursor is obtained. Step 2, Pre-calcination: After removing the nickel-based composite electrode precursor from the pressing mold, place it in a heating furnace and heat it to 400-600°C in an air atmosphere at a heating rate of 2-5°C / min. Maintain the temperature at 400-600°C for 1-3 hours for pre-calcination, and then cool it to room temperature with the furnace to obtain the pre-calcined product. Step 3, High-temperature flash calcination: Place the pre-calcined product in the middle of the carbon material, place it in a heating furnace, connect the two ends of the carbon material to electrodes, apply current to the carbon material in a vacuum environment, control the heating rate to be 20~500℃ / s, raise the temperature to 1500~3000℃ and hold for 1~60s for high-temperature flash calcination, then stop applying current, cool down to room temperature at a cooling rate of 100~1000℃ / s to obtain the product after high-temperature flash calcination; Step 4, Low-temperature annealing: The product after high-temperature flash calcination is placed in a heating furnace and heated to 300-1400℃ in air at a heating rate of 2-5℃ / min. It is then held at 300-1400℃ for 0.5-20h for low-temperature annealing, and then cooled to room temperature at a cooling rate of 2-5℃ / min to obtain a nickel-based composite electrode.
[0056] This invention combines pre-sintering, high-temperature flash sintering, and low-temperature annealing, and by controlling these conditions within the aforementioned range, it suppresses nickel enrichment at the electrolyte grain boundaries in the electrode, thereby improving the ionic conductivity at the grain boundaries. Simultaneously, it allows for a higher nickel content within the electrolyte grains (especially those using YSZ as the electrolyte), exhibiting characteristics of a mixed-ion conductor; it also ensures uniform grain size, improving the electrode's microstructure; and it reduces the risk of electrode cracking or deformation. Furthermore, most existing sintering methods require long sintering times (10-40 hours) at 1400-1800℃, resulting in high energy consumption. Compared to existing sintering methods, this invention offers advantages such as simple process, short sintering time, high efficiency, and reduced energy consumption, achieving energy-saving effects.
[0057] According to a specific embodiment of the second aspect of the present invention, the present invention provides a nickel-based composite electrode, which is prepared by the above-described method for preparing a nickel-based composite electrode.
[0058] In some embodiments, the difference between the Ni content at the grain boundaries of the electrolyte and the Ni content in the grains of the nickel-based composite electrode is less than 6%.
[0059] In some embodiments, the Ni content in the electrolyte grains of the nickel-based composite electrode is 1-15%, preferably 2-14%.
[0060] This invention can suppress nickel enrichment at grain boundaries in the electrode, thereby significantly improving the ionic conductivity at the grain boundaries. Simultaneously, the electrolyte grains in the nickel-based composite electrode of this invention can have a high nickel content, resulting in a significant increase in both ionic and electronic conductivity, exhibiting characteristics of a mixed ionic conductor. Therefore, the nickel-based composite electrode of this invention possesses improved conductivity and overall performance.
[0061] The technical solutions of the present invention are specifically illustrated by the following embodiments, but the present invention is not limited to these embodiments. Of course, various modifications can be made within the scope of the key points of the present invention.
[0062] Test method: Nickel enrichment at the grain boundaries of the electrolyte in nickel-based composite electrodes: Using an FEI Titan G2 60–300 microscopy at 300 kV, STEM-HAADF (scanning transmission electron microscopy-high angle annular dark field) images and EDS-mapping (energy dispersive spectroscopy-mapping) images of the electrode samples were obtained. The presence of nickel enrichment at the grain boundaries of the electrolyte in the electrode was analyzed by observing the STEM-HAADF and EDS-mapping images.
[0063] The difference between the Ni content at the grain boundaries and the Ni content in the grains of the electrolyte in the nickel-based composite electrode: Using the aforementioned instruments and testing conditions, an EDS-mapping diagram was obtained. The Ni content at the grain boundaries and the Ni content in the grains were determined using the EDS-mapping diagram and the instrument's built-in software. The difference was then obtained by subtracting the two. The Ni content was calculated based on the total atomic weight of all metallic elements as 100%.
[0064] Ni content in the electrolyte grains of the nickel-based composite electrode: EDS-mapping diagrams were obtained using the instruments and testing conditions described above. The Ni content in the grains was determined using the EDS-mapping diagrams and the instrument's built-in software. The Ni content was calculated based on the total atomic weight of all metal elements as 100%.
[0065] Example 1
[0066] Step 1: Mixing and Molding: Weigh NiO and YSZ at a mass ratio of 20:80, then add them to a ball mill jar. Add starch and anhydrous ethanol. Compared to the total amount of 100 parts by mass of NiO and YSZ, the amount of starch added is 10 parts and the amount of anhydrous ethanol added is 100 parts. After adding the grinding beads, place the mixture in a ball mill and grind it evenly. Then pour it out and dry it to obtain a mixture powder containing nickel compound and electrolyte. Then add the mixture powder containing nickel compound and electrolyte to an agate grinding ball and grind it evenly. Weigh an appropriate amount of the mixture powder and place it in a tableting mold. After pressing it into tablets under 80 MPa, the nickel-based composite electrode precursor is obtained. Step 2, Pre-calcination: After the nickel-based composite electrode precursor is removed from the pressing mold, it is placed in a heating furnace and heated to 500°C in air at a heating rate of 2°C / min. It is then pre-calcined at 500°C for 2 hours and then cooled to room temperature with the furnace to obtain the pre-calcined product. Step 3, High-temperature flash calcination: Fold the carbon fiber felt in half and place the pre-calcined product in the middle of the carbon fiber felt. Place it in a heating furnace and connect the two ends of the carbon fiber felt to electrodes. In a vacuum environment, apply current to the carbon fiber felt and control the heating rate to be 200℃ / s. Heat to 1700℃ and hold for 15s for high-temperature flash calcination. Then stop applying current and cool down to room temperature at a cooling rate of 800℃ / s to obtain the product after high-temperature flash calcination, which is denoted as 20N-YSZ-UHS. Step 4, Low-temperature annealing: Place the product after high-temperature flash calcination in a heating furnace and heat it to 800°C in air at a heating rate of 5°C / min. Hold it at 800°C for 2 hours for low-temperature annealing, and then cool it to room temperature at a cooling rate of 5°C / min to obtain a nickel-based composite electrode, denoted as 20N-YSZ-UHS-800; or, place the product after high-temperature flash calcination in a heating furnace and heat it to 1200°C in air at a heating rate of 5°C / min. Hold it at 1200°C for 2 hours for low-temperature annealing, and then cool it to room temperature at a cooling rate of 5°C / min to obtain a nickel-based composite electrode, denoted as 20N-YSZ-UHS-1200.
[0067] Figure 1STEM-HAADF images and EDS-mapping images of the grains and grain boundaries of the two nickel-based composite electrodes prepared in this embodiment. Figure 1 In the diagram, 'a' represents the STEM-HAADF plot and EDS-mapping plot of 20N-YSZ-UHS-800. Figure 1 In the diagram, b represents the STEM-HAADF plot and EDS-mapping plot of 20N-YSZ-UHS-1200. Figure 1 It can be seen that there is no Ni enrichment at the YSZ grain boundaries of 20N-YSZ-UHS-800 and 20N-YSZ-UHS-1200.
[0068] In this embodiment, the Ni content at the grain boundaries of the electrolyte in the 20N-YSZ-UHS-800 is 15.6%, and the Ni content in the grains is 13.7% (based on the total atomic weight of Ni, Y, and Zr being 100%), with a difference of 1.9%. In the 20N-YSZ-UHS-1200, the Ni content at the grain boundaries of the electrolyte is 14.3%, and the Ni content in the grains is 9.1% (based on the total atomic weight of Ni, Y, and Zr being 100%), with a difference of 5.2%. Therefore, this embodiment can eliminate Ni enrichment at the YSZ grain boundaries in the electrode, thereby improving the ionic conductivity at the grain boundaries. Furthermore, the electrolyte grains in the nickel-based composite electrode of this embodiment have a high nickel content, resulting in significantly increased ionic and electronic conductivity, exhibiting characteristics of a mixed ionic conductor.
[0069] In contrast. Figure 2 The images show STEM-HAADF and EDS-mapping diagrams of the YSZ grain boundaries in a commercially available SOFC anode support. It can be seen that significant Ni enrichment exists at the YSZ grain boundaries in the fuel electrode prepared using existing sintering methods.
[0070] Example 2
[0071] Step 1: Mixing and Molding: Weigh NiO and GDC at a mass ratio of 20:80, then add them to a ball mill jar. Add starch and anhydrous ethanol. The amount of starch added is 10 parts and the amount of anhydrous ethanol is 100 parts compared to the total amount of 100 parts by mass of NiO and GDC. After adding the grinding beads, place the mixture in a ball mill and grind it evenly. Then pour it out and dry it to obtain a mixture powder containing nickel compound and electrolyte. Then add the mixture powder containing nickel compound and electrolyte to an agate grinding medium and grind it evenly. Weigh an appropriate amount of the mixture powder and place it in a tableting mold. After pressing it into tablets under 80 MPa, the nickel-based composite electrode precursor is obtained. Step 2, Pre-calcination: After the nickel-based composite electrode precursor is removed from the pressing mold, it is placed in a heating furnace and heated to 500°C in air at a heating rate of 2°C / min. It is then pre-calcined at 500°C for 2 hours and then cooled to room temperature with the furnace to obtain the pre-calcined product. Step 3, High-temperature flash calcination: Fold the carbon fiber felt in half and place the pre-calcined product in the middle of the carbon fiber felt. Place it in a heating furnace and connect the two ends of the carbon fiber felt to electrodes. In a vacuum environment, apply current to the carbon fiber felt and control the heating rate to be 200℃ / s. Heat to 1500℃ and hold for 15s for high-temperature flash calcination. Then stop applying current and cool down to room temperature at a cooling rate of 800℃ / s to obtain the product after high-temperature flash calcination, which is denoted as 20N-GDC-UHS. Step 4, Low-temperature annealing: The product after high-temperature flash calcination is placed in a heating furnace and heated to 800°C in air at a heating rate of 5°C / min. It is then held at 800°C for 2 hours for low-temperature annealing, and then cooled to room temperature at a cooling rate of 5°C / min to obtain a nickel-based composite electrode, denoted as 20N-GDC-UHS-800.
[0072] Figure 4 In the figure, 'a' represents the STEM-HAADF image and EDS-mapping image of the nickel-based composite electrode at the grain boundaries and grains in this embodiment. Figure 4 As can be seen from 'a', there is no Ni enrichment at the GDC grain boundaries of 20N-GDC-UHS-800.
[0073] In this embodiment of the 20N-GDC-UHS-800, the Ni content at the grain boundaries of the electrolyte is 1.1%, and the Ni content in the grains is 2.3% (based on the total atomic weight of Ni, Gd, and Ce being 100%), with a difference of 1.2%. Therefore, the Ni content at the electrolyte grain boundaries in the nickel-based composite electrode of this embodiment is reduced, eliminating Ni enrichment at the GDC grain boundaries in the electrode and improving ionic conductivity.
[0074] Example 3
[0075] This embodiment is basically the same as Embodiment 1, except that: Step 3, high-temperature flash calcination: Fold the carbon fiber felt in half and place the pre-calcined product in the middle of the carbon fiber felt. Place it in a heating furnace, connect the two ends of the carbon fiber felt to electrodes, and apply current to the carbon fiber felt in a vacuum environment. Control the heating rate to 300℃ / s, raise the temperature to 2000℃ and hold for 2s for high-temperature flash calcination, then stop applying the current and cool it to room temperature at a cooling rate of 800℃ / s to obtain the product after high-temperature flash calcination. The remaining steps are the same as in Embodiment 1, except that the low-temperature annealing temperature is 800℃.
[0076] Figure 5In this embodiment, 'a' represents the STEM-HAADF and EDS-mapping images of the grains and grain boundaries of the nickel-based composite electrode. The Ni content at the grain boundaries of the electrolyte in this embodiment's nickel-based composite electrode is 15.7%, while the Ni content within the grains is 13.2% (based on a total atomic weight of Ni, Y, and Zr of 100%), a difference of 2.5%. There is no Ni enrichment at the YSZ grain boundaries of the nickel-based composite electrode in this embodiment. Furthermore, the electrolyte grains in this embodiment have a high nickel content.
[0077] Example 4
[0078] This embodiment is basically the same as Embodiment 1, except that: Step 3, high-temperature flash calcination: Fold the carbon fiber felt in half and place the pre-calcined product in the middle of the carbon fiber felt. Place it in a heating furnace, connect the two ends of the carbon fiber felt to electrodes, and apply current to the carbon fiber felt in a vacuum environment. Control the heating rate to be 20℃ / s, raise the temperature to 1500℃ and hold for 15s for high-temperature flash calcination. Then stop applying the current and cool down to room temperature at a cooling rate of 300℃ / s to obtain the product after high-temperature flash calcination. The remaining steps are the same as in Embodiment 1, except that the low-temperature annealing temperature is 1200℃.
[0079] Figure 6 In the figure, 'a' represents the STEM-HAADF and EDS-mapping images of the grains and grain boundaries of the nickel-based composite electrode in this embodiment. The Ni content at the grain boundaries of the electrolyte in the nickel-based composite electrode of this embodiment is 15.1%, and the Ni content in the grains is 12.8% (based on the total atomic weight of Ni, Y, and Zr being 100%), with a difference of 2.3%. There is no Ni enrichment at the YSZ grain boundaries of the nickel-based composite electrode in this embodiment. Furthermore, the electrolyte grains in the nickel-based composite electrode of this embodiment have a high nickel content.
[0080] Comparative Example 1
[0081] This comparative example is basically the same as Example 1, except that: the carbon fiber felt is folded in half, and the pre-calcined product is placed in the middle of the carbon fiber felt. It is then placed in a heating furnace, and electrodes are connected to both ends of the carbon fiber felt. In an air atmosphere, an electric current is applied to the carbon fiber felt, controlling the heating rate at 200°C / s. The temperature is raised to 1500°C and held for 15 seconds for high-temperature flash calcination. Then, the current is stopped, and the temperature is lowered to room temperature at a rate of 800°C / s to obtain the product after high-temperature flash calcination. The remaining steps are the same as in Example 1, except that the low-temperature annealing temperature is 1200°C.
[0082] Figure 7Figure 'a' shows the STEM-HAADF and EDS-mapping images of the nickel-based composite electrode in this comparative example at the grain boundaries and the grain size. In this comparative example, the Ni content at the grain boundaries of the electrolyte in the nickel-based composite electrode is 9.5%, while the Ni content in the grains is 1.4% (based on a total atomic weight of Ni, Y, and Zr of 100%), a difference of 8.1%. This indicates that the use of an air atmosphere during the flash calcination process in this comparative example affects the diffusion of Ni into the grains.
[0083] Comparative Example 2
[0084] This comparative example is basically the same as Example 1, except for the following step: High-temperature flash calcination: Fold the carbon fiber felt in half and place the pre-calcined product in the middle of the carbon fiber felt. Place it in a heating furnace, connect electrodes to both ends of the carbon fiber felt, and apply current to the carbon fiber felt in a vacuum environment. Control the heating rate at 300℃ / s, raise the temperature to 1500℃ and hold for 15s for high-temperature flash calcination. Then stop applying the current and cool it to room temperature at a rate of 5℃ / s to obtain the product after high-temperature flash calcination. The remaining steps are the same as in Example 1, except that the low-temperature annealing temperature is 1200℃.
[0085] Figure 8 Figure 'a' shows the STEM-HAADF and EDS-mapping images of the nickel-based composite electrode in this comparative example at the grain boundaries and the crystallite. The Ni content at the grain boundaries of the electrolyte in this comparative example's nickel-based composite electrode is 15.3%, while the Ni content in the grains is 2.1% (based on a total atomic weight of Ni, Y, and Zr of 100%), a difference of 13.2%. It can be seen that the excessively low cooling rate and prolonged cooling time in this comparative example resulted in Ni enrichment at the YSZ grain boundaries of the nickel-based composite electrode and an excessively low nickel content within the electrolyte grains.
[0086] Comparative Example 3
[0087] This comparative example prepared 20% NiO-doped YSZ using a conventional sintering method, including the following steps: Step 1: Mixing and Molding: Weigh NiO and YSZ at a mass ratio of 20:80, then add them to a ball mill jar. Add starch and anhydrous ethanol. Compared to the total amount of 100 parts by mass of NiO and YSZ, the amount of starch added is 10 parts and the amount of anhydrous ethanol added is 100 parts. After adding the grinding beads, place the mixture in a ball mill and grind it evenly. Then pour it out and dry it to obtain a mixture powder containing nickel compound and electrolyte. Then add the mixture powder containing nickel compound and electrolyte to an agate grinding ball and grind it evenly. Weigh an appropriate amount of the mixture powder and place it in a tableting mold. After pressing it into tablets under 80 MPa, the nickel-based composite electrode precursor is obtained. Step 2, Pre-firing, sintering and annealing: After the nickel-based composite electrode precursor is removed from the pressing mold, it is placed in a heating furnace and heated to 500°C in air at a heating rate of 2°C / min. It is then held at 500°C for 2 hours for pre-firing. After that, it is heated to 1400°C at a heating rate of 3°C / min and held at 1400°C for 10 hours. Then, it is cooled to 300°C at a cooling rate of 3°C / min and held at 300°C for 2 hours for low-temperature annealing. Finally, it is cooled to room temperature in the furnace to obtain the nickel-based composite electrode, denoted as 20N-YSZ.
[0088] In this comparative example, the Ni content at the grain boundaries of the electrolyte in the nickel-based composite electrode is 9.6%, while the Ni content in the grains is 1.2% (based on the total atomic weight of Ni, Y, and Zr being 100%), with a difference of 8.4%. It can be seen that Ni enrichment exists at the YSZ grain boundaries in this comparative example's nickel-based composite electrode, and the nickel content inside the electrolyte grains is too low.
[0089] Comparative Example 4
[0090] This comparative example prepared 20% NiO-doped GDC using a conventional sintering method, including the following steps: Step 1: Mixing and Molding: Weigh NiO and GDC at a mass ratio of 20:80, then add them to a ball mill jar. Add starch and anhydrous ethanol. The amount of starch added is 10 parts and the amount of anhydrous ethanol is 100 parts compared to the total amount of 100 parts by mass of NiO and GDC. After adding the grinding beads, place the mixture in a ball mill and grind it evenly. Then pour it out and dry it to obtain a mixture powder containing nickel compound and electrolyte. Then add the mixture powder containing nickel compound and electrolyte to an agate grinding medium and grind it evenly. Weigh an appropriate amount of the mixture powder and place it in a tableting mold. After pressing it into tablets under 80 MPa, the nickel-based composite electrode precursor is obtained. Step 2, Pre-firing, sintering and annealing: After the nickel-based composite electrode precursor is removed from the pressing mold, it is placed in a heating furnace and heated to 500°C in air at a heating rate of 2°C / min. It is then held at 500°C for 2 hours for pre-firing. After that, it is heated to 1400°C at a heating rate of 3°C / min and held at 1400°C for 10 hours. Then, it is cooled to 300°C at a cooling rate of 3°C / min and held at 300°C for 2 hours for low-temperature annealing. Finally, it is cooled to room temperature in the furnace to obtain the nickel-based composite electrode, denoted as 20N-GDC.
[0091] In this comparative example, the Ni content at the grain boundaries of the electrolyte in the nickel-based composite electrode is 5.3%, while the Ni content in the grains is 1.1% (based on the total atomic weight of Ni, Gd, and Ce being 100%), with a difference of 4.2%. It can be seen that Ni enrichment exists at the GDC grain boundaries in this comparative example's nickel-based composite electrode, and the nickel content inside the electrolyte grains is too low.
[0092] Test case
[0093] The nickel-based composite electrodes prepared in the above examples and comparative examples were subjected to electrochemical impedance spectroscopy (EIS) testing. The testing procedure included using a Gamry electrochemical workstation with a frequency of 0.01 Hz to 100,000 Hz.
[0094] Figure 3 To be respectively at 200℃ ( Figure 3 a) 800℃ Figure 3 Electrochemical impedance spectroscopy (EIS) spectra of 20N-YSZ from Comparative Example 3 and 20N-YSZ-UHS-800 and 20N-YSZ-UHS-1200 from Example 1 were obtained under conditions b) in [the following section]. Figure 3 It can be seen that the resistance of the YSZ grain boundaries in the nickel-based composite electrode of Example 1 is reduced, while the conductivity is increased. This demonstrates that eliminating the enrichment of Ni at the YSZ grain boundaries in the nickel-based composite electrode can significantly improve the conductivity of the grain boundaries.
[0095] Figure 4 b and c in the figure are 200℃ ( Figure 4 (b) 800℃ Figure 4 The electrochemical impedance spectroscopy spectra of the 20N-GDC in Comparative Example 4 and the 20N-GDC-UHS-800 in Example 2 were obtained under conditions c) in [the following text is missing]. Figure 4 It can be seen that the resistance of the GDC grain boundaries in the nickel-based composite electrode of Example 2 is reduced and the conductivity is increased.
[0096] Therefore, no Ni enrichment was found at the YSZ and GDC grain boundaries in the nickel-based composite electrode prepared by the method of this embodiment of the invention. Figure 1 and Figure 4 (a) Comparing the electrochemical impedance spectroscopy results of the nickel-based composite electrode of the present invention with those of the nickel-based composite electrode prepared by conventional sintering methods, it can be found that the conductivity of the YSZ and GDC grain boundaries is significantly improved ( Figure 3 and Figure 4 (b and c in the text).
[0097] Figure 5In Figure b, the electrochemical impedance spectroscopy of the nickel-based composite electrode of Example 3 was obtained at 250°C. It can be seen that the rapid sintering at ultra-high temperature for a short time gives the electrode a low ionic resistance. Figure 6 In Figure b, the electrochemical impedance spectroscopy of the nickel-based composite electrode of Example 4 was obtained at 250°C. It can be seen that reducing the heating rate does not affect the ionic resistance of rapid sintering, which is still lower than that of conventional sintering. Figure 7 In Figure b, the electrochemical impedance spectroscopy of the nickel-based composite electrode of Comparative Example 1 was obtained at 250°C. It can be seen that the air atmosphere affects the ionic resistance of rapid sintering, which is lower than that of conventional sintering. Figure 8 In Figure b, the electrochemical impedance spectroscopy of the nickel-based composite electrode of Comparative Example 2 was obtained at 250 °C. It can be seen that a low cooling rate will affect the ionic resistance of rapid sintering, which is close to that of conventional sintering.
[0098] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above descriptions are merely specific embodiments of the present invention and are not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a nickel-based composite electrode, comprising the following steps: (1) A mixture containing nickel compound and electrolyte is molded to obtain a nickel-based composite electrode precursor; (2) The nickel-based composite electrode precursor is pre-fired, then flash-fired at 1500~3000℃, and then annealed to obtain the nickel-based composite electrode. In step (2), the high-temperature flash burning is achieved by Joule heating. The high-temperature flash burning includes the following process: the pre-burned product is placed in the middle of the carbon material, an electric current is applied to the carbon material, the heating rate is controlled at 20~500℃ / s, the temperature is raised to 1500~3000℃ and held for 1~60s for high-temperature flash burning, then the current is stopped, and the temperature is cooled to room temperature at a cooling rate of 100~1000℃ / s to obtain the product after high-temperature flash burning.
2. The method for preparing the nickel-based composite electrode according to claim 1, wherein, In step (1), the nickel compound includes nickel oxide.
3. The method for preparing the nickel-based composite electrode according to claim 1, wherein, In step (1), the electrolyte is an electrolyte used in solid oxide batteries.
4. The method for preparing the nickel-based composite electrode according to claim 3, wherein, In step (1), the electrolyte includes one or more of yttrium-stabilized zirconium oxide, gadolinium-doped cerium oxide, scandium-stabilized zirconium oxide, samarium-doped cerium oxide, and perovskite oxide.
5. The method for preparing the nickel-based composite electrode according to claim 4, wherein, In step (1), the electrolyte comprises yttrium-stabilized zirconium oxide and / or gadolinium-doped cerium oxide.
6. The method for preparing the nickel-based composite electrode according to claim 1, wherein, In step (1), the mass ratio of the nickel compound to the electrolyte is (10~80):(90~20).
7. The method for preparing the nickel-based composite electrode according to claim 1, wherein, In step (2), the pre-firing temperature is 400~600℃, the pre-firing time is 1~3h, and the pre-firing is carried out in an oxidizing gas atmosphere.
8. The method for preparing the nickel-based composite electrode according to claim 1, wherein, In step (2), the annealing temperature is 300~1400℃, the annealing time is 0.5~20h, and the annealing is carried out in an oxidizing gas atmosphere.
9. A nickel-based composite electrode, which is prepared by the method of any one of claims 1-8, wherein the difference between the Ni content at the grain boundaries of the electrolyte and the Ni content in the grains of the nickel-based composite electrode is less than 6%.
10. The nickel-based composite electrode according to claim 9, wherein, The Ni content in the electrolyte grains of the nickel-based composite electrode is 1-15%.
Citation Information
Patent Citations
Method for modifying solid oxide fuel cell
CN117438624A